Initial evidence on the impact of the 2023 World Tennis Number algorithm change for predicting match outcomes - Krall, N.; Maroulis, N.; Mayew, R.; Mayew, W. (Coaching and Sport Science Review, 2025)
The World Tennis Number (WTN) algorithm was changed in 2023. We examine 2,956 matches from the United States Tennis Association (USTA) Junior National Championships to ascertain whether this algorithm change improved the ability of WTN to accurately classify match winners. We assess improvement relative to two benchmarks: Universal Tennis Rating (UTR) values and WTN values prior to the algorithm change. Existing research establishes that UTR and WTN exhibit equivalent classification accuracy for match outcomes and we find no evidence in any tournament division that the algorithm change improves WTN relative to UTR. When we compare classification accuracy of WTN values under the new algorithm to WTN values prior to the algorithm change, we find a statistically significant improvement in only one of four tournament divisions. The overall evidence is most consistent with statements by the USTA that within a player`s network, little accuracy improvement may be observed from the WTN algorithm change. Our findings update prior literature on the classification accuracy of UTR and WTN and provide a new reference point for evaluating future algorithm changes.